"Vi förstår, du behöver inte översätta" - Anna Sandell (Educare)
The overall aim of this article is to contribute with a pupils’ perspective on bilingual education, as well as their views on the mother tongue teachers who taught them. Swedish schools are exploring bilingual education because pupils with migration background do not perform as well as pupils with non-migration background. Beside the reason of employing mother tongue teachers for language support, earlier research suggests three dominating motives for employing teachers with migration backgrounds: supporting school success, creating role models, and bridging the gap between families and school. The empirical study consists of interviews with nine pupils in a class of 19, contextualized by a few weeks spent in their class. Results suggest that from the pupils’ perspective the mother tongue teacher does not add anything besides the language support. However, pupils are clear about these teachers’ importance for language development, and thereby their own school development. Furthermore they feel that knowledge development only takes place when classes are held in Swedish. It thus appears that schools have failed to convey that the mother tongue is just as important for the pupils as Swedish. A key conclusion is that schools need to enhance the status of different languages within the school context.